SHIFT OF REGULATION NORMS RELATING TO HOUSING LAW - Fanny, Fanny; harahap, irawan; azmi, bahrum (EKSEKUSI, 2024)
There is a shift in norms regarding the form of sanction regulation in the new and old public housing and settlement regulations, namely in Law Number 1 of 2011 concerning Housing and Settlement Areas to Law Number 6 of 2023 concerning Determination of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation Becomes Law. It seems that such conditions do not provide enough legal protection for consumers. The aim of this research is to analyze the ideal of establishing legal norms in housing regulations; to discover the legal implications of shifting norms regarding Housing. This type of research is normative legal research. The approach used is a statutory, concept and case approach with qualitative analysis methods. The results of the research show that ideally the establishment of legal norms is to regulate criminal sanctions, fines and additional criminal sanctions in Law Number 1 of 2011 concerning Housing and Settlement Areas. Where the criminal sanction of a fine has been applied to the developer of the Padang District Court in Decision Number 46/Pid.Sus/2018/PN Pdg which made the defendant admit that he felt deterred and provided justice and legal protection for low-income people regarding the right to livable government subsidized housing . The implications are: First, justice in the principles of this theory is as if it sides with the interests of business actors. Second, the failure of the law to regulate sanctions in the new regulations. This condition shows that there is an inconsistency between law in abstract form and the implementation of law in society. Third, the new regulation is in conflict vertically with Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Fourth, the new regulation is also horizontally in conflict with Law Number 12 of 2011 concerning the Establishment of Legislative Regulations as guidelines. making laws and regulations in Indonesia where the concept of Omnibuslaw is unknown in the types and hierarchy of laws and regulations in Indonesia and amendments/revocations of laws and regulations across sectors that are not justified, apart from that it also violates the principle of clarity of formulation and the principle of conformity between types and hierarchies. , and cargo material. Fifth, the shift in norms for regulating sanctions in the new regulations has the implication of not realizing legal protection for low-income communities who suffer losses due to developers and violating the community's human rights to obtain adequate residential housing.Keywords: Displacement, Sanctions, Housing.